Efficacy of radiofrequency ablation for metastatic papillary thyroid cancer with and without initial biochemical complete status - Chen, Wen-Chieh; Chou, Chen-Kai; Chang, Yen-Hsiang; Chiang, Pi-Ling; Lim, Lay-San; Chi, Shun-Yu; Luo, Sheng-Dean; Lin, Wei-Che (Frontiers in Endocrinology, 2022)
Abstract Objective: The application of radiofrequency ablation (RFA) for recurrent thyroid cancer has been demonstrated to effectively manage lesions at critical locations, such as abutting the trachea, with limited complications. Comprehensive investigation of both biochemical (B) and structural (S) change after RFA remains limited. We herein present the first single-center experience of RFA for the treatment of locoregional recurrent thyroid cancer in Taiwan. Design: 23 patients were enrolled, and the treatment responses after RFA were divided into four groups (E, S(+), B(+), and SB(+)), and then compared. The RFA technique, follow-up strategy, changes in pre-and post-operative status, and complications are presented. The volume reduction rate at 1, 3, and 6 months, and the differing responses between lesions abutting/not abutting the trachea are also discussed. Results: In patients with pre-RFA structural and biochemical incomplete (SB(+)) status, presenting with lesion with an initial maximum diameter of >3.2cm, a higher rate of structural incomplete status at the 6-month follow-up was noted in ROC analysis, with a sensitivity of 57% and specificity of 91%. Favorable structural remission after RFA was noted, and 60.9% of patients achieved biochemical complete status. No significant correlation was noted between the trachea-abutted lesion number and complete remission (p= 0.474). No significant difference in RFA efficacy was noted between the lesions abutting/not abutting the trachea. Conclusions: This retrospective study reveals that RFA can achieve both structural and biochemical improvements for locoregionally recurrent thyroid cancer, with a low complication rate. Nearly half of the patients achieved an excellent response after RFA, while a favorable treatment response can be achieved despite the lesion abutting the trachea, with a mean VRR of 84.74%.